Vetal Dev Temple - Mumbai Archive Project Team (Jio Institute, 2024)
The Vetal Dev Temple is dedicated to Panyatla Vetal and Aagya Vetal. The temple also houses the mother goddesses Sakhba Devi, Golfa Devi, and Harba Devi. The stone images are coated in thick layers of vermillion.